Teoría de la disuasión y la policía municipal en México - Willy W. Cortez (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2023)
– Based on Deterrence Theory, this essay evaluates the effectiveness of Mexico's municipal police to face common crime. According to the theory, police's deterrent capacity is complemented by two other actors: The Public Prosecutor Office and the Penal Justice System. We estimate a model where the common crime depends on deterrent capacity of municipal police, the probabilities of arrest and conviction, income inequality, poverty and municipality's size. By grouping municipalities into high- and low- crime units, we can analyze whether the crime gap between these two groups is associated to differences in their respective covariates, or their covariates' marginal contribution, or the interaction between them. The methodology is no other than an application of the Oaxaca-Blinder decomposition method for panel data.
Keywords: 330; Municipal Police; Common crimes; Deterrence Theory; Decomposition Oaxaca-Blinder for panel data; México